Lithium ion battery

By adding compound X to the electrolyte of the lithium-ion battery and adjusting the oil absorption value of the negative electrode silicon-based material, the structural damage and thermal runaway caused by volume changes during the charging and discharge process of silicon-doped negative electrode lithium-ion battery is solved, and the furnace temperature safety of the battery is improved.

CN119890404AActive Publication Date: 2025-04-25ZHUHAI COSMX BATTERY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411983060.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-25
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

Silicon-doped negative electrode lithium-ion batteries cause structural damage and material peeling due to volume changes during charging and discharging, which affects the service life and reliability of the battery, and has the risk of thermal runaway and explosion, affecting the safety of the furnace temperature.

Method used

By adding compound X to the electrolyte and adjusting the ratio of the oil absorption value of the negative electrode silicon-based material to the content of compound X, the ratio of A/M is within the range of 2.5×10-3≤A/M≤0.17, to improve the furnace temperature safety performance of the battery.

Benefits of technology

It improves the furnace temperature safety of the battery, suppresses the expansion of the negative electrode, reduces polarization and enhances the thermal stability of the battery, thereby improving the safety performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005221954650000071
    Figure BDA0005221954650000071
  • Figure BDA0005221954650000171
    Figure BDA0005221954650000171
  • Figure BDA0005221954650000172
    Figure BDA0005221954650000172
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion batteries, and provides a lithium ion battery. The battery comprises a positive plate, a negative plate and electrolyte, the negative plate comprises a negative current collector and a negative active material layer arranged on at least one side surface of the negative current collector, the negative active material layer comprises a negative active material, and the negative active material comprises a silicon-based material; the oil absorption value of the silicon-based material is recorded as M mL / 100 g; the electrolyte comprises a first additive, the first additive comprises a compound X, and based on the total mass of the electrolyte, the mass ratio of the compound X is marked as A%; a and M satisfy 2.5 * 10 <-3 > < = A / M < = 0.17, and the furnace temperature safety performance of the battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a lithium ion battery. Background Art

[0002] Silicon-doped anodes are considered to be one of the important directions for the development of future battery technology due to their high energy density, potential low cost and broad application prospects. However, challenges such as the stability of electrode materials, the maturity of preparation processes and commercial scale still need to be overcome in order to achieve their widespread application and commercial success in the market. At present, the main challenges include the volume expansion problem caused by silicon-containing anodes. Silicon undergoes significant volume changes during the battery charging and discharging process, which makes the electrodes containing silicon-containing anode materials more prone to structural damage and material stripping during the cycle process. These problems may limit the service life and reliability of the battery, especially under high power output or frequent charging and discharging conditions; the battery may also cause thermal runaway or even explosion during charging and use due to the expansion of silicon, affecting the furnace temperature safety of the battery. At present, furnace temperature safety is still one of the important issues that need to be solved in the research and development and commercialization of silicon-doped anode lithium-ion batteries. Summary of the invention

[0003] The purpose of the present invention is to overcome the above-mentioned problems existing in the prior art and to provide a lithium-ion battery. By adding compound X to the electrolyte and adjusting the ratio of the oil absorption value of the negative electrode silicon-based material to the content of compound X, the furnace temperature safety performance of the battery can be improved.

[0004] In order to achieve the above object, the present invention provides a lithium ion battery, the battery comprising a positive electrode sheet, a negative electrode sheet and an electrolyte;

[0005] The negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer disposed on at least one side of the negative electrode current collector, wherein the negative electrode active material layer comprises a negative electrode active material, and the negative electrode active material comprises a silicon-based material; the oil absorption value of the silicon-based material is recorded as M mL / 100g;

[0006] The electrolyte includes a first additive, the first additive includes a compound X, and the mass proportion of the compound X is recorded as A% based on the total mass of the electrolyte; the chemical formula of the compound X is shown in Formula I:

[0007] Formula I: Wherein, R1, R2, R3, and R4 independently include hydrogen atoms, substituted or unsubstituted alkane groups, substituted or unsubstituted olefin groups, substituted or unsubstituted aromatic groups, halogen substituents, and cyano groups; if substituted, the substituents are halogen or cyano groups; n satisfies: 1≤n≤20;

[0008] A and M meet: 2.5×10-3 ≤A / M≤0.17.

[0009] The present invention adopts the above technical solution to achieve the following beneficial effects:

[0010] The lithium ion battery provided by the present invention can improve the furnace temperature safety of the battery by adjusting the ratio of the oil absorption value of the silicon-based material to the content of the compound X when a specific relationship is satisfied.

[0011] The endpoints and any values ​​of the range disclosed in this article are not limited to the precise range or value, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. Herein, in the absence of special instructions, data ranges include endpoints. DETAILED DESCRIPTION

[0012] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0013] Unless otherwise defined, all scientific and technical terms used in the present invention have the same meanings as commonly understood by one of ordinary skill in the art to which the present invention relates.

[0014] In the present invention, the terms "battery", "lithium battery", "lithium-ion battery" and "lithium-ion secondary battery" all have the same meaning and refer to lithium-ion secondary batteries, which generally include an electrode assembly (such as a positive electrode sheet, a negative electrode sheet and a separator), a container (shell) for accommodating the electrode assembly, and an electrolyte.

[0015] In the present invention, the term "alkane group" refers to a group formed by an alkane molecule losing one or more hydrogen atoms, in which the carbon atoms in the molecule are connected by carbon-carbon single bonds, for example, methyl (CH3-), ethyl (C2H5-), etc.

[0016] In the present invention, the alkane group may be substituted with a halogen or a cyano group. When a hydrogen atom in an alkane group is substituted with a halogen, a halogenated alkane group is formed. For example, when a hydrogen atom of a methyl group (CH3-) is substituted with a chlorine group, a chloromethyl group (CH2Cl-) is formed. When a hydrogen atom in an alkane group is substituted with a cyano group, a cyanoalkane group is formed. For example, when a hydrogen atom of an ethyl group (C2H5-) is substituted with a cyano group, a cyanoethyl group (NCC2H4-) is formed.

[0017] In the present invention, the term "olefin group" refers to a group formed by an olefin molecule losing one or more hydrogen atoms, and the structure contains a carbon-carbon double bond, for example, vinyl (CH2=CH-) and the like.

[0018] In the present invention, the olefin group may be substituted with a halogen or a cyano group. When a hydrogen atom in an olefin group is substituted with a halogen, a halogenated olefin group is formed. For example, when a hydrogen atom of a vinyl group (CH2=CH-) is substituted with chlorine, a chlorovinyl group (such as CH2=CCl-) is formed. When a hydrogen atom in an olefin group is substituted with a cyano group, a cyanoolefin group is formed. For example, when a hydrogen atom of a vinyl group is substituted with a cyano group, a cyanovinyl group (CH2=CHCN) is formed.

[0019] In the present invention, the term "aromatic group" refers to a phenyl group or a group obtained by replacing some of the hydrogen atoms on the phenyl group, and can also be understood as a group formed by aromatic hydrocarbons losing hydrogen atoms on the benzene ring. For example, it can be phenyl (Ph-), p-methylphenyl (-Ph-CH3), etc.

[0020] In the present invention, the aromatic group can be replaced by halogen or cyano. When the hydrogen atom on the aromatic group is replaced by halogen, a halogenated aromatic group is formed. For example, when a hydrogen atom of phenyl (Ph-) is replaced by chlorine, chlorophenyl (-Ph-Cl) is formed. If the substitution occurs in the para position of the methyl group, when a hydrogen atom of p-methylphenyl (-Ph-CH3) is replaced by chlorine, p-chloromethylphenyl (-Ph-CH3, one H of Ph is replaced by Cl) is formed. When the hydrogen atom on the aromatic group is replaced by cyano, a cyano aromatic group is formed. For example, when a hydrogen atom of phenyl is replaced by cyano, benzocyano (Ph-CN) is formed. Similarly, if a hydrogen atom (hydrogen on the non-methyl group) of p-methylphenyl is replaced by cyano, the corresponding cyano p-methylphenyl is formed.

[0021] In the present invention, the term "halogen substituent" refers to the case where a halogen atom F, Cl, or Br is used as a substituent group.

[0022] In the present invention, the term "cyano" refers to a substituent group containing a cyano group (-CN).

[0023] The present invention provides a lithium ion battery, the battery comprising a positive electrode sheet, a negative electrode sheet and an electrolyte;

[0024] The negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer disposed on at least one side of the negative electrode current collector, wherein the negative electrode active material layer comprises a negative electrode active material, and the negative electrode active material comprises a silicon-based material; the oil absorption value of the silicon-based material is recorded as M mL / 100g;

[0025] The electrolyte includes compound X, and the mass proportion of compound X is recorded as A% based on the total mass of the electrolyte; the chemical formula of compound X is shown in formula I:

[0026] Formula I: Wherein, R1, R2, R3, and R4 independently include hydrogen atoms, substituted or unsubstituted alkane groups, substituted or unsubstituted olefin groups, substituted or unsubstituted aromatic groups, halogen substituents, and cyano groups; if substituted, the substituents are halogen or cyano groups; n satisfies: 1≤n≤20;

[0027] A and M meet: 2.5×10 -3 ≤A / M≤0.17.

[0028] Illustratively, n in the chemical formula I is an integer, for example, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, or 20.

[0029] The present invention can improve the wettability of the electrolyte and increase the liquid retention of the battery by adjusting the oil absorption value of the negative electrode silicon-based material. Compound X can form a film at the negative electrode, and a suitable oil absorption value can make the negative electrode silicon-based material fully infiltrated by the electrolyte, increase the contact area of ​​compound X at the negative electrode, and in the process of forming the SEI film, the SEI film can be more firmly combined with the negative electrode, thereby improving the structural stability of the SEI film; the oil absorption value of the negative electrode silicon-based material is coordinated with the mass proportion of compound X in the electrolyte, and a larger oil absorption value of the negative electrode silicon-based material helps compound X to form a more stable and dense SEI film at the negative electrode, inhibit the expansion of the silicon-containing negative electrode, reduce polarization heat generation, and improve the thermal stability of the battery, thereby jointly improving the furnace temperature safety of the battery.

[0030] In the present invention, the mass proportion A of compound X in the electrolyte and the oil absorption value M of the silicon-based material satisfy: 2.5×10 -3 ≤A / M≤0.17, the value of A / M can be, for example, 0.0025, 0.004, 0.006, 0.008, 0.01, 0.03, 0.05, 0.07, 0.1, 0.13, 0.15, 0.17 or any point value in the range of the above two point values. At this time, the electrolyte wettability can be improved so that compound X forms a more stable SEI film at the negative electrode, alleviates the expansion of the negative electrode, reduces polarization heat generation, and improves the battery furnace temperature safety. At the same time, A and M satisfy the above relationship, which can avoid A / M>0.17, the oil absorption value of the silicon-based material is too small, resulting in insufficient electrolyte wettability of the battery under high temperature conditions or the mass proportion of compound X in the electrolyte is low, and a stable and firm SEI film cannot be formed, and the battery furnace temperature safety is poor; it can also avoid A / M<2.5×10 -3When the oil absorption value of the silicon-based material is too high, it will cause uneven distribution of the negative electrode material, thereby causing uneven distribution of the electrolyte, resulting in unstable battery performance and affecting the battery's cycle performance.

[0031] In some embodiments, the mass ratio A of the compound X in the electrolyte and the oil absorption value M of the silicon-based material satisfy 5×10 -3 ≤A / M≤0.1;

[0032] In some embodiments, the oil absorption value M of the silicon-based material satisfies: 10≤M≤100. The oil absorption value of the silicon-based material can be, for example, 10mL / 100g, 20mL / 100g, 30mL / 100g, 40mL / 100g, 50mL / 100g, 60mL / 100g, 70mL / 100g, 80mL / 100g, 90mL / 100g, 100mL / 100g, or any point value in the range consisting of any two of the above point values.

[0033] Exemplarily, the test method of the oil absorption value M may include the following steps: weigh the mass of a clean beaker and a glass rod as m1, record the total mass after adding 5 g of the composite material as m2, add dioctyl phthalate (DOP) dropwise with a titration bottle, and stir thoroughly, stop adding DOP when a lump is formed, weigh the total weight of the beaker at this time as m3, and the oil absorption value M = (m3-m2) / (m2-m1)×100.

[0034] In some embodiments, the mass percentage A% of compound X in the electrolyte satisfies: 0.1≤A≤5, for example, it can be 0.1, 0.2, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5 or any point value in the range consisting of any two of the above point values; in one example, A satisfies: 0.5≤A≤2.

[0035] When the above range is met, the silicon-based material can better cooperate with the compound X in the electrolyte, provide good wettability for the electrolyte, and promote the compound X to form a more stable and firm SEI film at the negative electrode, inhibit the expansion of the negative electrode, reduce polarization heat generation, and improve the furnace temperature safety of the battery.

[0036] In some embodiments, the compound X represented by Formula I comprises at least one of the following compounds:

[0037]

[0038] Among them, the compound X represented by formula I-1 is preferred.

[0039] Further selecting the compound X shown above, the chemical bonding effect of compound X in the negative electrode is stronger, making the SEI film stronger, and the fluoride layer formed by compound X can further improve the strength of the SEI film, improve the performance of the interface film, and better inhibit the expansion of the battery negative electrode during the charge and discharge cycle, thereby improving the battery cycle stability and improving the battery furnace temperature safety.

[0040] In some embodiments, the Dv50 of the silicon-based material is recorded as Cμm; the electrolyte includes a second additive, and the second additive includes a sulfur-containing additive; the mass proportion of the sulfur-containing additive based on the total mass of the electrolyte is recorded as B%; the sulfur-containing additive includes at least one of 1,3-propane sultone (PS), vinyl sulfate (DTD), and vinyl sulfite (ES); A, B, and C satisfy: 0.01≤(A+B) / C≤2, and the value of (A+B) / C can be, for example, 0.01, 0.02, 0.05, 0.1, 0.3, 0.5, 0.7, 1, 1.3, 1.5, 1.7, 2 or any point value in the range composed of any two of the above point values. In the electrolyte, the combination of sulfur-containing additives and compound X can form a more solid composite SEI film at the negative electrode. On the one hand, it can more effectively inhibit the volume expansion of the negative electrode during the cycle, further improving the furnace temperature safety of the battery. On the other hand, since compound X has a greater impact on the SEI film impedance, the addition of sulfur-containing additives can also reduce the impact of compound X on the SEI film impedance, increase the lithium ion deintercalation rate, and improve the low-temperature performance of the battery. When the mass proportion of compound X and sulfur-containing additives in the electrolyte further satisfies the above relationship with the Dv50 of the silicon-based material, the particle size of the silicon-carbon material can provide a suitable specific surface area, further increase the electrolyte infiltration contact area, increase the number of reaction active sites, and facilitate the formation of sulfur-containing additives and compound X at the negative electrode, further reduce the interface impedance during the battery charge and discharge process, and further improve the low-temperature cycle stability of the battery.

[0041] In some embodiments, the sulfur-containing additive is vinyl sulfate. When the sulfur-containing additive is vinyl sulfate, it can form a smoother and more uniform composite SEI film in combination with compound X, and the SEI film has higher compactness and stability, improves the high temperature resistance of the SEI film, and effectively improves the furnace temperature safety of the battery. At the same time, the use of vinyl sulfate reduces the impedance of the SEI film, further improving the low temperature cycle performance of the battery.

[0042] The possible mechanism is that compound X may copolymerize with the functional group of vinyl sulfate through its unsaturated bond to form a stable network structure, making the connection between SEI film layers more stable, further stabilizing the structure of the composite SEI film, and forming a smoother and more uniform SEI film. At the same time, the smooth and uniform composite SEI film can provide a smoother ion transmission channel, and at the same time, sulfide and other components are formed in the inorganic layer of the SEI film, which reduces the lithium ion transmission impedance, improves the contact and electronic transmission performance of the electrode / electrolyte interface, and reduces polarization, thereby improving the furnace temperature safety of the battery and the low-temperature cycle performance of the battery.

[0043] In some embodiments, A, B, and C satisfy: 0.2≤(A+B) / C≤1.5, and the value of (A+B) / C can be, for example, 0.2, 0.3, 0.5, 0.7, 0.9, 1.1, 1.3, 1.5 or any point value in the range of the above point values; when A, B, and C further satisfy the above range, the furnace temperature safety of the battery can be further improved, and the low-temperature cycle performance of the battery can be improved.

[0044] In some embodiments, the mass percentage of sulfur-containing additives B% satisfies: 0.05≤B≤10, for example, it can be 0.05, 0.1, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10 or any point value in the range of the above two points; in one example, B satisfies: 1≤B≤5. When the mass percentage of sulfur-containing additives further satisfies the above range, B<0.05 can be avoided, and too little sulfur-containing additives will lead to uneven SEI film when forming SEI film, which is not conducive to the improvement of battery cycle and thermal stability; it can also avoid that when B>10, the SEI film is too thick, resulting in excessive impedance of lithium-ion batteries and reduced low-temperature cycle performance of batteries.

[0045] In some embodiments, the Dv50(C) of the silicon-based material satisfies: 5≤C≤15, for example, it can be 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm or any point value in the range composed of any two of the above point values. In one example, the Dv50(C) of the silicon-based material satisfies: 6≤C≤10. When the Dv50 of the silicon-based material further meets the above range, it can avoid that when C>15μm, the particle size of the silicon-based material is too large, the silicon-carbon material produces a more drastic volume change during the charge and discharge process, and the SEI film formed by the compound X and the sulfur-containing additive cannot inhibit the volume expansion of the silicon-carbon particles, resulting in repeated rupture and growth of the SEI film, and the increase in the thickness of the SEI film deteriorates the low-temperature performance; it can also avoid that when C<5μm, the particle size of the silicon-based material is too small, resulting in the electrolyte being unable to well infiltrate the electrode, the SEI film formed by the compound X and the sulfur-containing additive at the negative electrode is not stable and firm enough, and the SEI film is more easily damaged by stress under high temperature conditions, which may cause a greater volume change of the negative electrode, affecting the structural stability of the battery, and further affecting the furnace temperature safety of the battery.

[0046] In some embodiments, the open pore volume of the silicon-based material is 0.0001 cm 3 / g-0.1cm 3 / g, for example, 0.0001 cm 3 / g, 0.0005cm 3 / g, 0.001cm 3 / g, 0.005cm 3 / g, 0.01cm 3 / g, 0.02cm 3 / g, 0.03cm 3 / g, 0.04cm 3 / g, 0.05cm 3 / g, 0.06cm 3 / g, 0.07cm 3 / g, 0.08cm 3 / g, 0.09cm 3 / g, 0.1cm 3 / g or any point value in the range of the above two point values. Preferably, the open pore volume of the silicon-based material is 0.0005cm 3 / g-0.05cm 3 / g. When the open pore volume of the silicon-based material further meets the above range, the larger the open pore volume, the more conducive it is to the electrolyte infiltration into the negative electrode, so that compound X and sulfur-containing additives can be better film-formed at the negative electrode; and the larger pore structure can provide a better heat dissipation path, thereby helping to reduce the risk of battery overheating. At the same time, it can avoid that the open pore volume is too large, which affects the film formation of compound X and sulfur-containing additives; avoid that the open pore volume is too small, which may lead to poor thermal dissipation and thermal conductivity of the negative electrode material. Under high power or high load conditions, the battery may generate too much heat, and the heat cannot be effectively dissipated, increasing overheating and safety risks, and affecting the safety of the battery furnace temperature.

[0047] Exemplarily, the open pore volume of silicon-based materials can be measured using a Tri StarⅡ specific surface analyzer. Specifically, the following steps may be included: crush the silicon-based material into powder, add a sample with a mass of about 1g to the sample tube, and weigh the sample and the sample tube. Then put the sample tube into a degassing station for degassing. After the degassing is completed, weigh the sample tube to obtain the mass of the degassed sample. Then use the specific surface analyzer, input the mass data of the sample, start the instrument to measure the sample, and the analyzer will automatically perform isothermal adsorption and desorption analysis, and calculate the specific surface area and open pore volume by measuring the amount of nitrogen adsorbed on the sample surface.

[0048] In some embodiments, the silicon content in the negative electrode active material is 1%-20%, for example, it can be 1%, 3%, 5%, 8%, 10%, 12%, 14%, 16%, 18%, 20% or any point value in the range of any two of the above points. In one example, the silicon-based material includes at least one of silicon carbon, silicon oxygen, silicon element, and silicon alloy. Preferably, the silicon-based material includes silicon carbon.

[0049] When the silicon content further meets the above range, the cycle stability and service life of the battery can be further improved, and the situation where the silicon content is too high, there is more silicon material, which leads to a large volume change in the negative electrode, causing the SEI film to be destroyed and reconstructed, resulting in continuous consumption of lithium ions, electrolyte decomposition and lithium deposition, which deteriorates the cycle performance of the battery; it also avoids the situation where the silicon content is too low and cannot meet the capacity requirements of the battery.

[0050] For example, the test method for the content of silicon in the present invention can be tested by thermogravimetric analysis, for example, using a Shimadzu DTG-60 thermogravimetric analyzer for testing, and the test conditions are: sample weight 5 mg, air as atmosphere, heating rate 10°C / min from room temperature to 900°C and constant temperature for 40 minutes. The relationship between the content of silicon (x) and the final weight residual percentage (y) of the entire test is: x=7y / 15.

[0051] In some embodiments, the negative electrode current collector includes a polymer layer and a conductive layer located on at least one side of the polymer layer.

[0052] In some embodiments, the polymer in the polymer layer is selected from at least one of polyethylene, polypropylene (PP), ethylene propylene copolymer, polyethylene terephthalate (PET), polyethylene naphthalate and poly(p-phenylene terephthalamide). The above polymer types have good insulation and chemical stability, and in the battery, they can prevent the internal short circuit of the battery and improve the mechanical strength of the battery to a certain extent.

[0053] In some embodiments, the thickness of the polymer is 2.5 μm-15 μm, for example, 2.5 μm, 2.6 μm, 2.7 μm, 2.8 μm, 2.9 μm, 3 μm, 3.2 μm, 3.4 μm, 3.6 μm, 3.8 μm, 4 μm, 8, 10, 12, 15 or any point value in the range of the above two points. The thickness of the polymer meets the above range, which can avoid the thickness of the polymer being too thick, resulting in obstruction of ion transmission, reduction of battery charge and discharge performance, increase of overall battery thickness, and reduction of battery energy density; it can avoid the thickness of the polymer being too thin, which can reduce the mechanical strength and chemical stability of the battery, reduce the battery cycle performance, and may also cause battery short circuit.

[0054] In some embodiments, the conductive layer includes one or both of copper or a copper alloy.

[0055] For example, the conductive layer can be obtained by vapor deposition or electroplating, and the thickness of the conductive layer can be adjusted by changing the deposition time or the electroplating time.

[0056] In some embodiments, the electrolyte further includes a third additive, the third additive includes at least one of a nitrile compound, an anhydride compound and fluoroethylene carbonate; in one example, based on the total mass of the electrolyte, the mass proportion of the third additive is 0.1%-15%, for example, it can be 0.1%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15% or any point value in the range composed of the above two point values. Nitrile compounds can improve the thermal stability and chemical stability of the electrolyte, thereby reducing the risk of thermal runaway when the battery is overcharged; anhydride compounds, as film-forming additives, can improve the formation of SEI film and increase the conductivity of the electrolyte; fluoroethylene carbonate can reduce the internal resistance of the battery, improve the battery charging and discharging performance, and enhance the stability and uniformity of the SEI film. Further adding the third additive to the electrolyte can further enhance the stability of the SEI film, improve the safety of the battery furnace temperature, improve the battery cycle stability, and enhance the battery performance.

[0057] In some embodiments, the electrolyte further comprises an organic solvent and an electrolyte lithium salt.

[0058] In some embodiments, the organic solvent comprises carbonate and / or carboxylate.

[0059] In some embodiments, the organic solvent comprises at least one of ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), ethyl propionate (EP), propyl propionate (PP), ethyl acetate (EA), ethyl butyrate (EB) and γ-butyrolactone (GBL).

[0060] In some embodiments, the electrolyte lithium salt includes at least one of lithium hexafluorophosphate (LiPF6), lithium difluorophosphate (LiPF2O2), lithium difluorobisoxalate phosphate (LiPF2(C2O4)2), lithium tetrafluorooxalate phosphate (LiPF4C2O4), lithium oxalate phosphate (LiPO2C2O4), lithium bisoxalatoborate (LiBOB), lithium difluorooxalatoborate (LiODFB), lithium tetrafluoroborate (LiBF4), lithium bistrifluoromethylsulfonyl imide (LiTFSI) and lithium bisfluorosulfonyl imide (LiFSI).

[0061] In some embodiments, the mass content of the electrolyte lithium salt is 10%-15% based on the total mass of the electrolyte, for example, 10%, 11%, 12%, 13%, 14% or 15%.

[0062] In some embodiments, the negative electrode active material further includes a carbon-based material.

[0063] In some embodiments, the carbon-based material comprises at least one of natural graphite, artificial graphite, mesocarbon microbeads, soft carbon, hard carbon, and graphene.

[0064] In some embodiments, the negative electrode active material layer further includes a negative electrode conductor and a negative electrode binder.

[0065] In some embodiments, based on the total mass of the negative electrode active material layer, the negative electrode active material comprises 80%-99.8% by mass of the negative electrode active material, 0.1%-10% by mass of the negative electrode conductor, and 0.1%-10% by mass of the negative electrode binder.

[0066] In one embodiment, the negative electrode conductive agent includes at least one of conductive carbon black, acetylene black, Ketjen black, conductive graphite, conductive carbon fiber, carbon nanotubes, metal powder, and carbon fiber.

[0067] In one embodiment, the negative electrode binder includes at least one of sodium carboxymethyl cellulose, styrene-butadiene latex, polytetrafluoroethylene, and polyethylene oxide.

[0068] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer coated on one side or both sides of the positive electrode current collector, and the positive electrode active material layer includes a positive electrode active material.

[0069] In some embodiments, the positive electrode active material includes LiNi x Co y Mn z M 1-x-y-z O2 or LiLPO4, wherein 0≤x≤1, 0≤y≤1, 0≤z≤1, 0≤x+y+z≤1, M includes at least one of Mn and Al, M includes at least one of Mg, Zn, Ga, Ba, Al, Fe, Cr, Sn, V, Sc, Ti, Nb, Mo, Zr, Ta, W, B, F, Si, and L includes at least one of Mn, Fe, and Co.

[0070] In some embodiments, the positive electrode active material layer further includes a positive electrode conductor and a positive electrode binder.

[0071] In some embodiments, based on the total mass of the positive electrode active material layer, the positive electrode active material comprises 80%-99.8% by mass of the positive electrode active material, 0.1%-10% by mass of the positive electrode conductive agent, and 0.1%-10% by mass of the positive electrode binder.

[0072] In some embodiments, the positive electrode conductive agent includes at least one of conductive carbon black, acetylene black, Ketjen black, conductive graphite, conductive carbon fiber, carbon nanotubes, and metal powder.

[0073] In some embodiments, the positive electrode binder includes at least one of sodium carboxymethyl cellulose, styrene-butadiene latex, polytetrafluoroethylene, and polyethylene oxide.

[0074] In some embodiments, the positive electrode current collector may be a positive electrode current collector conventionally used in the art, such as aluminum foil or a composite current collector.

[0075] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0076] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0077] The present invention is described in detail below in conjunction with specific embodiments, which are used to understand but not to limit the present invention.

[0078] Example 1-1

[0079] 1) Preparation of positive electrode

[0080] The positive electrode active materials lithium cobalt oxide (LiCoO2), polyvinylidene fluoride (PVDF), SP (super P) and carbon nanotubes (CNT) are mixed in a mass ratio of 96:2:1.5:0.5, N-methylpyrrolidone (NMP) is added, and the mixture is stirred under the action of a vacuum mixer until the mixed system becomes a positive electrode active slurry with uniform fluidity; the positive electrode active slurry is evenly coated on both surfaces of an aluminum foil; the coated aluminum foil is dried, and then rolled and cut to obtain the desired positive electrode sheet.

[0081] 2) Negative electrode preparation

[0082] The negative electrode active material artificial graphite is mixed with SiC mixture, sodium carboxymethyl cellulose (CMC-Na), styrene-butadiene rubber, conductive carbon black (SP) and single-walled carbon nanotubes (SWCNTs) in a mass ratio of 94.5:2.5:1.5:1:0.5, deionized water is added, and the negative electrode active slurry is obtained under the action of a vacuum mixer; the negative electrode active slurry is evenly coated on the two surfaces of the composite current collector (the polymer coating includes ethylene propylene copolymer, and the conductive layers on both sides are copper foil); the coated composite current collector is dried at room temperature, and then transferred to an oven at 80°C for drying for 10 hours, and then cold pressed and cut to obtain the negative electrode sheet.

[0083] 3) Preparation of electrolyte

[0084] In a glove box filled with argon (H2O<0.1ppm, O2<0.1ppm), EC, PC, DEC, and PP were mixed in a mass ratio of 10:20:40:30, and then fully dried lithium hexafluorophosphate (LiPF6) was quickly added thereto at a concentration of 1 mol / L. After dissolution, compound X (specific amount as described in Table 1) was added and stirred evenly. After passing the moisture and free acid tests, the desired electrolyte was obtained.

[0085] 4) The diaphragm was purchased from Asahi Chemical.

[0086] 5) Preparation of batteries

[0087] The positive electrode sheet of step 1), the negative electrode sheet of step 2) and the separator are stacked in the order of positive electrode sheet, separator and negative electrode sheet, and then wound to obtain a battery cell; the battery cell is placed in an outer packaging aluminum foil, and the electrolyte of step 3) is injected into the outer packaging, and the battery is obtained through vacuum packaging, standing, forming, shaping, sorting and other processes. The battery of the present invention has a charge and discharge range of 3.0V-4.5V.

[0088] Performance Testing:

[0089] i) 45℃ Cyclic Performance Test

[0090] The batteries obtained in the embodiments and comparative examples were charged and discharged at 45°C at a rate of 1C within the charge and discharge cut-off voltage range. The discharge capacity of the first week of the test was calculated as x1 mAh, and the discharge capacity of the Nth cycle was calculated as y1 mAh. The capacity of the Nth week was divided by the capacity of the first week to obtain the cycle capacity retention rate R1=y1 / x1 of the Nth week, and the cycle number of the battery when the cycle capacity retention rate R1 was 80% was recorded.

[0091] ii) Low temperature discharge capacity retention test

[0092] The battery obtained in the embodiment and the comparative example was charged and discharged for 5 times at a rate of 1C at -20°C, and then charged to 4.5V at a rate of 1C, and the 1C capacity Q0 was recorded. The fully charged battery was placed at -20°C for 4 hours, and then discharged to 3V at a rate of 0.2C, and the discharge capacity Q1 was recorded. The low-temperature discharge capacity retention rate can be calculated; low-temperature discharge capacity retention rate (%) = Q1 / Q0×100%

[0093] iii) Furnace temperature safety test

[0094] The embodiments and comparative examples were repeated 10 times. The fully charged batteries of each embodiment and comparative example were stored at 130° C. for 1 hour, and the number of batteries that did not catch fire or explode was observed.

[0095] The Example 1-2 group and the Comparative Example 1-4 were carried out with reference to the Example 1-1, and the main differences are shown in Table 1. Among them, the Example 1 group changed the mass proportion of compound X in the electrolyte (A). The Example 2 group changed the oil absorption value (M) of the silicon-based material. No compound X was added to the electrolyte of the Comparative Example 1. The Comparative Example 2 did not meet the formula range of A / M. The mass proportion of compound X in the Comparative Example 3 was too small. The mass proportion of compound X in the Comparative Example 4 was too large.

[0096] Table 1

[0097]

[0098]

[0099] Note: “ / ” in Table 1 means the corresponding data were not measured.

[0100] As shown in Table 1, the lithium ion battery provided by the present invention can improve the furnace temperature safety of the battery by adjusting the ratio of the oil absorption value of the silicon-based material to the content of the compound X, and the ratio of the content of the compound X to the oil absorption value of the silicon-based material.

[0101] Example 3 was carried out in accordance with Example 1-1, and the main differences are shown in Table 2. In particular, the type of compound X was changed in Example 3.

[0102] Table 2

[0103] Compound X type Furnace temperature passing rate Example 1-1 Formula I-1 10 / 10 Example 3-1 Formula I-3 8 / 10 Example 3-2 Formula I-4 8 / 10 Example 3-3 Formula I-1 and Formula I-3; the ratio of the two is 1:1 8 / 10

[0104] It can be seen from Table 2 that the change of the type of compound X in the present invention can achieve the effect of improving the furnace temperature safety of the battery. When the compound X represented by formula I-1 is used, the furnace temperature safety performance of the battery can be better improved.

[0105] The Example 4 group was carried out with reference to the Example 1-1, and the main differences are shown in Table 3. Among them, the Example 4 group changed the open pore volume of the silicon-based material.

[0106] Table 3

[0107]

[0108]

[0109] It can be seen from Table 3 that the present invention can help improve the heat dissipation and thermal conductivity of the silicon-based material and improve the safety of the battery furnace temperature by controlling the open pore volume of the silicon-based material within a suitable range.

[0110] The examples 5-8 were carried out with reference to the examples 1-1, and sulfur-containing additives were further added to the electrolyte. The main differences are shown in Table 4. Among them, the example 5 group changed the mass proportion of sulfur-containing additives in the electrolyte (B). The example 6 group changed the Dv50 (C) of the silicon-based material. The value of (A+B) / C in the example 7 was not within the protection range. The example 8 used conventional copper foil for the negative electrode current collector.

[0111] Table 4

[0112]

[0113] As can be seen from Table 4, the present invention can improve the furnace temperature safety performance of the battery, improve the high temperature cycle performance of the battery, and take into account the low temperature performance of the battery by adding a sulfur-containing additive to the electrolyte and controlling the ratio of the sum of the mass proportion of compound X and the mass proportion of the sulfur-containing additive in the electrolyte to the Dv50 of the silicon-based material.

[0114] It should be noted that, in this article, the terms "comprise", "include" or any other variant thereof are intended to cover non-exclusive inclusion, so that the process, method, article or device including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise one..." do not exclude the presence of other identical elements in the process, method, article or device including the element. In addition, it should be pointed out that the scope of the methods and devices in the embodiments of the present application is not limited to performing functions in the order shown or discussed, and may also include performing functions in a substantially simultaneous manner or in reverse order according to the functions involved, for example, the described method may be performed in an order different from that described, and various steps may also be added, omitted, or combined. In addition, the features described with reference to certain examples may be combined in other examples.

[0115] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A lithium ion battery, characterized in that: The lithium-ion battery comprises a positive electrode sheet, a negative electrode sheet and an electrolyte; The negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer disposed on at least one side of the negative electrode current collector, wherein the negative electrode active material layer comprises a negative electrode active material, and the negative electrode active material comprises a silicon-based material; the oil absorption value of the silicon-based material is recorded as M mL / 100g; The electrolyte includes a first additive, the first additive includes a compound X, and the mass proportion of the compound X is recorded as A% based on the total mass of the electrolyte; the chemical formula of the compound X is shown in Formula I: Formula I: Wherein, R1, R2, R3, and R4 independently include hydrogen atoms, substituted or unsubstituted alkane groups, substituted or unsubstituted olefin groups, substituted or unsubstituted aromatic groups, halogen substituents, and cyano groups; if substituted, the substituents are halogen or cyano groups; n satisfies: 1≤n≤20; A and M meet: 2.5×10 -3 ≤A / M≤0.

17.

2. The lithium-ion battery according to claim 1, characterized in that A and M meet: 5×10 -3 ≤A / M≤0.1; and / or, M satisfies: 10≤M≤100; And / or, A satisfies: 0.1≤A≤5; Preferably, A satisfies 0.5≤A≤2.

3. The lithium-ion battery according to claim 1, characterized in that The compound X shown in formula I includes at least one of the following compounds:

4. The lithium-ion battery according to claim 1, characterized in that: The Dv50 of the silicon-based material is denoted as C μm; The electrolyte includes a second additive, and the second additive includes a sulfur-containing additive; based on the total mass of the electrolyte, the mass proportion of the sulfur-containing additive is recorded as B%; A, B, and C satisfy: 0.01≤(A+B) / C≤2.

5. The lithium-ion battery according to claim 4, characterized in that: The sulfur-containing additive includes at least one of 1,3-propane sultone, vinyl sulfate, and vinyl sulfite.

6. The lithium-ion battery according to claim 4, characterized in that: A, B, C satisfy: 0.2≤(A+B) / C≤1.5; And / or, B satisfies: 0.05≤B≤10; Preferably, B satisfies: 1≤B≤5; And / or, C satisfies: 5≤C≤15.

7. The lithium-ion battery according to claim 1, characterized in that: The open pore volume of the silicon-based material is 0.0001 cm 3 / g-0.1cm 3 / g; Preferably, the open pore volume of the silicon-based material is 0.0005 cm 3 / g-0.05cm 3 / g.

8. The lithium-ion battery according to claim 1, characterized in that The negative electrode current collector comprises a polymer layer and a conductive layer located on at least one side of the polymer layer; Preferably, the polymer in the polymer layer is at least one selected from polyethylene, polypropylene, ethylene propylene copolymer, polyethylene terephthalate, polyethylene naphthalate and poly(p-phenylene terephthalamide); Preferably, the polymer layer has a thickness of 2.5 μm-15 μm.

9. The lithium-ion battery according to claim 1, characterized in that: The content of silicon in the negative electrode active material is 1%-20%; And / or, the silicon-based material includes at least one of silicon carbon, silicon oxygen, silicon element, and silicon alloy; Preferably, the silicon-based material comprises silicon carbon.

10. The lithium ion battery according to any one of claims 1 to 9, characterized in that: The electrolyte further includes a third additive, wherein the third additive includes at least one of a nitrile compound, an acid anhydride compound and fluoroethylene carbonate; Preferably, based on the total mass of the electrolyte, the mass proportion of the third additive is 0.1%-15%.

Citation Information

Patent Citations

  • Secondary battery and device

    CN117525594A

  • Ultrahigh-structure and high-specific-surface carbon black based on high crystallinity, preparation method of ultrahigh-structure and high-specific-surface carbon black, electrode slurry and battery

    CN118398815A

  • Eddy current array probe for inspection

    KR102214144B1